Exploring the Origins of Western Constitutional Culture in the Bible - QIAO Fei (Journal of Research for Christianity in China (JRCC), 2025)
It is widely accepted in academia that constitutional culture originated in ancient Greece. However, biblical research reveals that the constitutional concepts and practices of the ancient Israelite kingdom predate this. Political power in ancient Israel was divided into three branches: the monarchy, the priesthood, and the prophetic office. These powers maintained a system of checks and balances, with royal authority particularly constrained by the priesthood and prophetic office. Kings, priests, prophets, and the common people were all bound to exercise their powers under the law, which held supreme authority. Thus, the ancient Israelite kingdom constituted a “constitutional” state. This “constitutional” ideology and practice profoundly influenced Western legal civilization through the dissemination of the Christian Bible.